2020
DOI: 10.1177/0731121419899387
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Social Control: Racial Resentment, Punitiveness, and White Support for Spending on Law Enforcement

Abstract: A well-established body of research finds that racial resentment predicts support for punitive criminal justice policy. This article links racial resentment with punitiveness, expanding the existing research—a body of work that largely treats punitivity as a response to threat. Data for this study come from three nationally representative samples and incorporate individual and contextual factors. Key variables include Racial Resentment, Political Ideology, Punitiveness, Crime—both objective crime (i.e., county… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…By extension, per the racial animus model, racial resentment should be a primary factor that shapes attitudes toward the police. This matches what several recent studies found: Racial resentment is associated with pro-policing attitudes (Strickler & Lawson, 2020), with greater support for spending on law enforcement (Morris & LeCount, 2020), and with support for aggressive policing . Given the racialized nature of policing and the fact that many Americans believe the police treat citizens of different races unequally (Shaw & Brannan, 2009;Weitzer & Tuch, 2006), it is reasonable to expect that racial animus will shape attitudes toward protest policing in a similar way as it shapes attitudes toward policing more generally.…”
Section: Theoretical and Empirical Backgroundsupporting
confidence: 90%
“…By extension, per the racial animus model, racial resentment should be a primary factor that shapes attitudes toward the police. This matches what several recent studies found: Racial resentment is associated with pro-policing attitudes (Strickler & Lawson, 2020), with greater support for spending on law enforcement (Morris & LeCount, 2020), and with support for aggressive policing . Given the racialized nature of policing and the fact that many Americans believe the police treat citizens of different races unequally (Shaw & Brannan, 2009;Weitzer & Tuch, 2006), it is reasonable to expect that racial animus will shape attitudes toward protest policing in a similar way as it shapes attitudes toward policing more generally.…”
Section: Theoretical and Empirical Backgroundsupporting
confidence: 90%
“…Those Black officers who had experienced racial discrimination (e.g., racial profiling, subject to police violence) either before or during their tenure as officers, in contrast, hold more critical views of policing (i.e., racial justice oriented). Along somewhat similar lines, Morris and LeCount (2020), drawing on three national survey samples, found an important link between racial resentment and punitiveness and police spending. Such work suggests a complex interplay of racial attitudes and policing that our data are unable to address but that we hope future scholarship will be able to explore.…”
Section: Discussionmentioning
confidence: 71%
“…Other scholars have come to similar conclusions, arguing that racial resentment is an effective measure of racial prejudice (DeSante 2013; Tarman and Sears 2005), but critics of the scale contend that the endogeneity between racial attitudes and political ideologies limits its ability to accurately capture racial prejudice (see Sniderman and Tetlock 1986). Nonetheless, racial resentment remains one of the most popular means of studying racial attitudes in the social sciences, and several studies have used it to examine the relationship between racial attitudes and punitive sentiment (Bobo and Johnson 2004;Carter and Corra 2016;Green, Staerkle, and Sears 2006;Morris and LeCount 2020).…”
Section: Racial Resentment and Punitive Attitudesmentioning
confidence: 96%
“…Research examining racial attitudes and punitive sentiment has (to our knowledge) uniformly found negative attitudes toward blacks to be strongly correlated with higher levels of punitiveness. For instance, Morris and LeCount (2020) observe that racial resentment is associated with support for increased spending on law enforcement. Carter and Corra (2016) find that racial resentment is a significant predictor of whites' attitudes regarding police use of force.…”
Section: Racial Resentment and Punitive Attitudesmentioning
confidence: 99%